Design as a critical research - Calejo, Marta (2016)
Historically the imaginary and the hegemonic thinking, in the Western globe north, has been marked by the epistemology and capitalists archetypes. Notwithstanding the design seem as a practice and discipline shielded on a simplistic discourse of functional / communicative efficiency, wandering through by multiple aestheticism apparently neutral in relation to the symbolic, but in fact they never are, because what really hapens is that the aesthetic appearance of the generated forms will always be a review of the powers ruling. We start from the understanding that the act of creating an aesthetic artifact, will also be a movement of inscription in a discursive platform (that precedes it), is in itself an narrative act and that fact represent a certain take place in relation to certain symbolic reality. On reflection shown if it sees design as a discipline and / or an instrument of action, whose operational relevance tends to question and simultaneously rehearsing a response, in which more than why interests answer to why. Apparently the design is a content mediator, but also, it is structure, is body, is idea. We think a design praxis as discipline and enrollment tool of critical thought and social transformation. For guiding research in this text, we propose the following question: Can the Design want for themselves an engagement with the symbolic in order to be an active part in the production of critical thinking in the place where it belongs? Methodologically our argument will be present in two differents moments: 1. a first, exploratory nature where we rescue the draw issues in the practice of design and 2. a second analytical nature concerning the subject issues (graphic and / or utility ) design and how it incorporates formal rites, political events and social practices of contemporary everyday life. We consider the praxis of design as a discipline and critical thinking enrollment tool as agents of social transformation. With this study we seek for contribute phenomenology design by studying the artifacts of configuration as well as the possible messages they convey and what impact they may have on the social network.